Impact of multilateral trade liberalization on resource revenue - Sèna Kimm Gnangnon; Jean-François Brun (Economies, 2018)
This paper investigates the impact of multilateral trade liberalization on resource revenue, using an unbalanced panel dataset comprising 57 countries, including both developed and developing countries, over the period 1995-2015. By means of the two-step system Generalized Methods of Moments (GMM) estimator, the empirical analysis suggests that multilateral trade liberalization exerts a negative effect on resource revenue, probably at the benefit of non-resource revenue. However, this effect over the full sample hides a positive effect of multilateral trade liberalization on resource revenue in poorest countries, and a negative effect of multilateral trade liberalization on resource revenue in non-poorest countries of the sample. Additionally, the negative effect of multilateral trade liberalization on resource revenue over the full sample appears to be dependent on the degree of domestic trade liberalization. In fact, multilateral trade liberalization genuinely induces a reducing effect on resource revenue only if countries liberalize their domestic trade regime beyond a minimum level.
Keywords: H2; Q28; Q33; F14; 330; resource revenue; multilateral trade liberalization; public revenue diversification